2018
DOI: 10.14506/ca33.1.01
|View full text |Cite
|
Sign up to set email alerts
|

Sounds of Democracy: Performance, Protest, and Political Subjectivity

Abstract: This article asks a deceptively simple question: what does democracy sound like? Democracy is commonly associated with various forms of voicing—political speeches, shouting protesters, filibusters in the halls Congress, or heated debates in teashops, salons, and newspapers around the world. Voice thus often functions as a metaphor for political participation and representation. Political metaphors of voice are usually disembodied, and are rarely invoked in reference to the other forms for political utterance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 22 publications
0
25
0
2
Order By: Relevance
“…These works are linked to a related question of publics and audience, as Shankman () explored through an analysis of the public anthropology of Margaret Mead. Several broke new ground in engaging directly with sound as an object of ethnographic inquiry, either as a means to analyze democratic protest and the “roar of the crowd” in Nepal (Kunreuther ), devotional poetry in Mauritius (Eisenlohr ), and state power through noise ordinances in urban Brazil (Cardoso ).…”
Section: On Staying With the Troubles Of Carceralitymentioning
confidence: 99%
See 1 more Smart Citation
“…These works are linked to a related question of publics and audience, as Shankman () explored through an analysis of the public anthropology of Margaret Mead. Several broke new ground in engaging directly with sound as an object of ethnographic inquiry, either as a means to analyze democratic protest and the “roar of the crowd” in Nepal (Kunreuther ), devotional poetry in Mauritius (Eisenlohr ), and state power through noise ordinances in urban Brazil (Cardoso ).…”
Section: On Staying With the Troubles Of Carceralitymentioning
confidence: 99%
“…In a necessary dialectic, much work considered seepage or failures of containment through analytics of freedom (Furani ), the unruly (Cooper ; J. Fisher ; Scherz , 108; Stoetzer , 302), zaniness (Degani ), play (Rea ), transgression (Muir and Gupta ), porousness (Bjork‐James ), madness (Nuhrat ), rupture or breaking open (Kunreuther ; Kyriakides ; Ofstehage ; Saleh ), queering (Heywood ; Shirinian ), invasion (Sherouse ), excess (Gershon ), or contagion (Kivland ; Luna ; Rubin ; Rubinstein et al. ).…”
mentioning
confidence: 99%
“…Ritual sonic objects at Syrian funerals also include nonvocal sounds, such as gunshots or the revving of motorcycle engines, that prostheticize the mourners' aural presence. This sonic "repertoire of contention" (Tufekci 2017, 89) is at once local and prescient to the political demands and emotions of the processional event and intersecting with broader geographies and longer histories of protests, whose repertoires are, as those working in sound studies have demonstrated, intertextual, subversive, and visceral (Kheshti 2015;Kunreuther 2018;Manabe 2015;Tausig 2019).…”
Section: Mourningmentioning
confidence: 99%
“…Making sounds enacts political presence both metaphorically and physically. At the Occupy Baluwatar protests in Nepal, political subjectivity forms through āwāj (voice)-a political allegory for democracy and an audible vocalization, sound, or noise that generates political presence (Kunreuther 2018). The "Human Mic" tactic deployed at Occupy Wall Street protests and rooftop chanting in Iran during the Green Revolution (Kheshti 2015), respectively, demonstrate the efficacy of vocal techniques to reclaim space from the state.…”
mentioning
confidence: 99%
“…For example, several studies that appeared in 2018 attend to the embodied materiality of voice to highlight the political and phenomenological consequences that derive from ideological conceptions of sound and the body. Kunreuther's () account of participatory democracy amidst the vibrant soundscapes of Kathmandu critiques the liberal notion of political voice that excludes from itself the embodied and the sonic, while Eisenlohr's () work on the performance of Muslim devotional prayers in the South Asian diaspora in Mauritius calls us to consider the phenomenologically felt body as a site for questioning the dichotomy of discursive signification and sonic materiality. Others pay attention to the interdiscursive processes that may take place cross‐medially and their effects on the constitution and reproduction of institutional power.…”
Section: Metasemiotic Chains Of Circulationmentioning
confidence: 99%